2005
DOI: 10.1074/jbc.m413014200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cysteinyl Leukotriene Type 1 Receptor Internalization and Signaling

Abstract: Cysteinyl leukotrienes activate the cysteinyl leukotriene type 1 receptor (CysLT1R) to regulate numerous cell functions important in inflammatory processes and diseases such as asthma. Despite its physiologic importance, no studies to date have examined the regulation of CysLT1R signaling or trafficking. We have established model systems for analyzing recombinant human CysLT1R and found regulation of internalization and signaling of the CysLT1R to be unique among G proteincoupled receptors. Rapid and profound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 58 publications
1
78
1
Order By: Relevance
“…In contrast to data recently published using a recombinant receptor system (Naik et al, 2005), we found that PKC was not involved in agonist-induced CysLT 1 receptor desensitization in dU937 cells. On the contrary, GRKs seem to be involved in this process, considering that in a stable U937 clone with reduced GRK2 expression (Fernandez et al, 2002) the rate of recovery of CysLT 1 functionality was faster than that in control U937 cells, and a GRK2 inhibitor partially reduced agonist-induced desensitization.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to data recently published using a recombinant receptor system (Naik et al, 2005), we found that PKC was not involved in agonist-induced CysLT 1 receptor desensitization in dU937 cells. On the contrary, GRKs seem to be involved in this process, considering that in a stable U937 clone with reduced GRK2 expression (Fernandez et al, 2002) the rate of recovery of CysLT 1 functionality was faster than that in control U937 cells, and a GRK2 inhibitor partially reduced agonist-induced desensitization.…”
Section: Discussioncontrasting
confidence: 56%
“…Such observations are typical of GPCRs. However, unlike many studies of GPCR desensitization (45)(46)(47), G2A desensitization was not accompanied by obvious loss of the receptor from the cell surface; rather, desensitization to lyso-PL stimulation was temporally associated with visible G2A patching (Fig. 8), perhaps the result of progressive receptor self-association (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…8; lyso-PC stimulation shown). Although receptor internalization has been reported as accompanying desensitization of many GPCRs following stimulation (45)(46)(47), the maintenance of elevated surface G2A through the period of functional desensitization suggested that G2A desensitization in neutrophils is more clearly associated with patching of the receptor than to its internalization. As such, we reasoned that any stimulus mobilizing secretory vesicles and patching G2A would lead to a nonresponsive state to subsequent lyso-PL stimulation.…”
Section: Lyso-pls Enhance Surface Localization and Redistribution Of mentioning
confidence: 99%
“…Full-length A2B adenosine receptor internalizes via an arrestin-dependent pathway, but deep truncation of its C-terminus redirects it to an arrestin-independent route (Matharu et al, 2001). The cysteinyl leukotriene type 1 receptor internalizes normally in mouse embryonic fibroblasts in which both non-visual arrestins are knocked out, yet arrestin overexpression enhances its internalization (Naik et al, 2005), apparently linking it to an additional arrestin-dependent pathway, similar to the situation with the m2 mAChR . The metabotropic glutamate receptor mGluR1a undergoes extensive constitutive agonist-independent internalization that does not involve arrestins, yet its internalization in response to agonist is selectively mediated by arrestin2 (Dale et al, 2001).…”
Section: Does Arrestin Binding Predetermine the Internalization Pathway?mentioning
confidence: 99%